2019
DOI: 10.1002/chem.201901808
|View full text |Cite
|
Sign up to set email alerts
|

Empowering Synthesis of Complex Natural Products

Abstract: Synthesis of natural products remains a daring task. Their richly diverse and intricate structures often encompass a large degree of unsaturation, contain fused and/or bridged rings, or possess numerous stereogenic centers. Thus, their preparation requires significant synthetic overhead, detracting from their overall practicality as well as hampering the ability of medicinal chemists to synthesize derivatives for pharmaceutical optimization and structure‐activity relationship studies. The purpose of this Minir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 89 publications
0
8
0
Order By: Relevance
“…Despite the tremendous advancements in the asymmetric and catalytic construction of carbonÀcarbon bondsa chieved during the last years, there is still an eed for versatile methods that will enablet he synthesis of ab road range of molecular architectures. [1][2][3] In this context,E vans [4] and Shibasaki [5] have convincingly established that both thiazolidinethione and azaindoline are suitable scaffolds to carry out direct and highly enantioselective aldol reactions catalyzed by chiral nickel(II) and copper(I) complexes, respectively.I nspired by such studies, we have recently reported that simple N-propanoyl-1,3-thiazinane-2-thione is av aluable platform from which to carry out direct and enantioselective carbonÀcarbon bond formingr eac-tions with ap lethora of cationic reagents using 1-5 mol %o f robust and easyt oh andle [(R)-DTBM-SEGPHOS]NiCl 2 . [6] Particularly,t he direct addition to trimethyl orthoformatea ctivated by TESOTf produces as ingle enantiomer of the corresponding adduct in 90 %y ield (Scheme 1A).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the tremendous advancements in the asymmetric and catalytic construction of carbonÀcarbon bondsa chieved during the last years, there is still an eed for versatile methods that will enablet he synthesis of ab road range of molecular architectures. [1][2][3] In this context,E vans [4] and Shibasaki [5] have convincingly established that both thiazolidinethione and azaindoline are suitable scaffolds to carry out direct and highly enantioselective aldol reactions catalyzed by chiral nickel(II) and copper(I) complexes, respectively.I nspired by such studies, we have recently reported that simple N-propanoyl-1,3-thiazinane-2-thione is av aluable platform from which to carry out direct and enantioselective carbonÀcarbon bond formingr eac-tions with ap lethora of cationic reagents using 1-5 mol %o f robust and easyt oh andle [(R)-DTBM-SEGPHOS]NiCl 2 . [6] Particularly,t he direct addition to trimethyl orthoformatea ctivated by TESOTf produces as ingle enantiomer of the corresponding adduct in 90 %y ield (Scheme 1A).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the tremendous advancements in the asymmetric and catalytic construction of carbon−carbon bonds achieved during the last years, there is still a need for versatile methods that will enable the synthesis of a broad range of molecular architectures . In this context, Evans and Shibasaki have convincingly established that both thiazolidinethione and azaindoline are suitable scaffolds to carry out direct and highly enantioselective aldol reactions catalyzed by chiral nickel(II) and copper(I) complexes, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Several compounds are tissue-specific accumulated, and are usually structurally complex (Armaly et al, 2015). Therefore it is necessary the use of chemical analysis techniques to isolate and identify the extracted plant metabolites (Hernandez & Sarlah, 2019). There are a few cases where the use of plant cell culture of Jatropha curcas has allowed the production of bioactive compounds (Alvero-Bascos & Ungson, 2012;Mahalakshmi, Eganathan & Parida, 2013;Nassar, El-Ahmay & Al-Azizi, 2013;Zaragoza-Martínez et al, 2016), the study of the culture at different stages of toxic and non-toxic varieties, generate the opportunity to design biotechnological models for production of bioactive compounds i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that the diversification of a common precursor into several synthetic intermediates is a powerful tool for synthesizing molecules otherwise difficult or impossible to reach, and the limited number of studies on the O -silyl migration in carbacyles, we set out to improve the selectivity of the migration process (Scheme d). This approach would provide us synthetically rich intermediates in a divergent synthesis strategy …”
mentioning
confidence: 99%